Online reputation management for dummies - Stradtman, Lori Randall (Hoboken, New Jersey John Wiley & Sons, Inc., 2012)
Managing your online reputation is more important than ever-- and here's how to do it! This guide helps you create a personalized preparedness system that not only helps you deal with online chatter, but also builds your online reputation.
Introduction -- Getting started with online reputation management -- Organizing your teams -- Listening is love -- Establishing your reputation -- Responding to crisis: your step-by-step plan -- The part of tens.
Includes index.
Keywords: Corporate image -- Computer network resources; Internet marketing; Internet in publicity; Social networks; Online identities